The distributional impact of tax and benefit reforms since 2010 - Tom Waters; Thomas Wernham (Institute for Fiscal Studies (IFS), 2024)
The past 14 years have witnessed an enormous amount of reform to the tax and benefit system. While it is tempting for politicians to draw attention to one set of reforms or another, what matters for household incomes is the whole system. In this report, we study the impact of policy changes to direct taxes (income tax, National Insurance contributions and council tax), indirect taxes (VAT, duties) and welfare benefits. We examine reforms implemented since 2010-11, as well as those that have been announced and (on current plans) will be implemented by 2027-28. As well as highlighting how these reforms have affected richer and poorer households, those of different ages, and different family types, we draw out some key themes that have emerged - intentionally or otherwise - from successive Chancellor's decisions. Whoever forms the next government, it is this tax and benefit system that they will inherit and which departures from will be measured against.
Keywords: 330; Poverty; inequality and social mobility; Taxes and benefits; Benefits; Income taxes; National Insurance contributions; Tax; Taxes on wealth and spending